A preliminary study for developing operator manual for ruminant abattoirs on prevention of foodborne diseases and halal compliance - ., Myat Min @ Mohd Omar; Hashi, Abdurezak Abdulahi; Abdul Wahab, Ridhwan; Shahdan, Intan Azura; Mohd Amin, Mohd Hishammfariz; Samsuddin, Niza (IIUM Press, 2018)
Introduction: Foodborne diseases (FBD) can occur along the whole series of food production from the sources and processing until serving for consumers. Among the sources of food, meat is a major concern since it is come from animal origin where the pathogens might transmit to human and/or contaminate microbes from infected meat handlers to consumers at any time. Background Study: Abattoir operators – managers and workers, and the authorities – Veterinary and Halal officers, play the key role in conversion of live food animals to healthy and edible halal meat and useful animal products fit for human consumption. Abattoir operators, abattoir operating procedures including animal handling and meat process need to abide the standard operating procedures (SOP) as guided by the authority for the safety of meat in meeting the requirements for public health. It is also to be in lines with the halal rules and regulations from the perspective of Islam so that to achieve halal food and products which are beneficial for both physical and spiritual. Problem Statement: A number of researches have conducted in the prevalence of FBD but lack of prevention with combination of halal-compliance especially in ruminant abattoir areas. Objective: The researcher aims to do preliminary study for developing the required Operator Manual of Ruminant Abattoirs (OMRA) on prevention of FBD and also for halal compliance. Method: This preliminary study will be looking into the process of ruminant abattoir by literature search if its premises, staffs, animal handling and the equipment used are in accordance with the halalcompliance and prevention of FBD. From visiting two abattoirs and online data sources, gathering relevant information for ruminant abattoir and halal meat of Malaysia is done. Results: Based on the preliminary findings, the three major accreditations of Malaysia which are MS1500:2009 guidelines of Department of Standards Malaysia, JAKIM (Jabatan Agama Kemajuan Islam Malaysia/ Department of Islamic Development Malaysia) 2008 & 2011 Malaysian halal meat protocols, and DVS (Department of Veterinary Services of Malaysia) code of veterinary practice 2012 respectively. They are compared and analyzed to get the required information for further developing OMRA for the benefits of meat industry, health ministry, global halal market authority and all consumers.